Field study of the Occupant's Thermal Preferences for Cooling in Living Rooms Based on Different Set Point Temperatures. Issue 1 (February 2021) - Kamaruddin, N I; Zaki, S A; Rijal, H B; Hagishima, A; Khalid, W; Atikha, N; Yakub, F; Redzuan, F L M
Abstract: The use of an air conditioner (AC) becomes essential in residential buildings, particularly in a hot and humid climate to optimize indoor thermal comfort. To accelerate the process of space cooling, occupants tend to use the lowest set point of the AC thermostat setting to achieve the desired thermal comfort in the indoor environment. A field study was conducted to investigate the occupants' thermal preferences in experimental living rooms at four AC set point temperatures (16°C, 20°C, 24°C, and 28°C). The indoor thermal environmental measurement and questionnaire survey were conducted on 63 respondents with 252 samples. The results of the thermal sensation vote (TSV) revealed that at the AC set point temperatures of 16°C and 20°C, 38% and 62% of the respondents voted 'cold', respectively. Meanwhile, they voted 'a bit warmer' for their thermal preference (TP). At the set point temperature of 24°C, 41% of the respondents voted 'neutral' for TSV, while 54% voted 'no change' for TP. At the same time, for the set point temperature of 28°C, 38% of the respondents voted 'slightly warm' for TSV and 'a bit cooler' for TP. In short, the respondent might have different thermal preferences even though they were experiencing the same thermal condition. This finding also indicated that there is a limit to how much the AC can provide uniform thermal satisfaction among occupants in the same room with a single control of the set point temperature.